A study of co-firing palm kernel shell on the Nagan Raya coal-fired power plant - Ansar, Khairil; Syuhada, Ahmad; Sofyan, Sarwo Edhy (Politeknik Negeri Lhokseumawe, 2023)
Co-firing biomass with coal in existing utility boilers is seen as one strategy for promoting renewable energy with low upfront costs and little to no impact on the boilers' high efficiency. The purpose of this research is to analyse the fuel characteristics and performance of palm kernel shell co-firing at Nagan Raya Coal-Fired Power Plant (CFPP) at various percentages of palm kernel shell combination. The analysis is conducted based on the operational data obtained from Nagan Raya Power Plant. In this study, the characteristics of fuel and the performance of a power plant are analysed based on percentages of fuel variations, namely 100% coal, 95% coal-5% palm kernel shell, and 90% coal-10% palm kernel shell. The results reveal that co-firing's biomass ratio boosted operation parameters, including main steam pressure, temperature, and flow rate. Subsequently, co-firing with 90% coal-10% palm kernel shell has enhanced the power plant output to 90,7 MW compared to those with 100% coal, 95% coal-5% palm kernel shell, namely 89,3 MW and 90,4 MW, respectively